Aromatic "Redox Tag"-assisted Diels–Alder reactions by electrocatalysis. Issue 10 (11th July 2016) - Okada, Yohei; Yamaguchi, Yusuke; Ozaki, Atsushi; Chiba, Kazuhiro
Abstract : Electrocatalytic Diels–Alder reactions have been designed and demonstrated based on the aromatic "redox tag" concept. Abstract : Electrocatalysis was employed to promote Diels–Alder reactions between electronically mismatched substrates. A catalytic amount of electricity was enough to complete the overall reactions and GC-MS monitoring and CV measurements clearly illustrated the electrocatalytic nature of the reactions, which involve an EC-backward-E mechanism. The electrocatalytic Diels–Alder reactions were rationally designed based on the concept of redox tags. The results were supported by DFT calculations.